Modelling in the evaluation of a manufacturing strategy - Baines, Tim S. (Cranfield University, 1994)
This thesis describes research that has developed the principles of a modelling tool for the analytical evaluation of a manufacturing strategy. The appropriate process of manufacturing strategy formulation is based on mental synthesis with formal planning processes supporting this role. Inherent to such processes is a stage where the effects of alternative strategies on the performance of a manufacturing system must be evaluated so that a choice of preferred strategy can be made. Invariably this evaluation is carried out by practitioners applying mechanisms of judgement, bargaining and analysis. Ibis thesis makes a significant and original contribution to the provision of analytical support for practitioners in this role. The research programme commences by defining the requirements of analytical strategy evaluation from the perspective of practitioners. A broad taxonomy of models has been used to identify a set of potentially suitable techniques for the strategy evaluation task. Then, where possible, unsuitable modelling techniques have been identified on the basis of evidence in the literature and discarded from this set. The remaining modelling techniques have been critically appraised by testing representative contemporary modelling tools in an industrially based experimentation programme. The results show that individual modelling techniques exhibit various limitations in the strategy evaluation role, though some combinations do appear to provide the necessary functionality. On the basis of this comprehensive and in-depth knowledge a modelling tool ' has been specifically designed for this task. Further experimental testing has then been conducted to verify the principles of this modelling tool. Ibis research has bridged the fields of manufacturing strategy formulation and manufacturing systems modelling and makes two contributions to knowledge. Firstly, a comprehensive and in-depth platform of knowledge has been established about modelling techniques in manufacturing strategy evaluation. Secondly, the principles of a tool that supports this role have been formed and verified.